Should You Allow Your Agent to Become Your Competitor? On Non-Compete Agreements in Employment Contracts - Matthias Kräkel; Dirk Sliwka (University of Bonn, Bonn Graduate School of Economics (BGSE), 2006)
We discuss a principal-agent model in which the principal has the opportunity to include a non-compete agreement in the employment contract. We show that if the agent faces limited liability and there is an incentive problem the principal prefers not to impose such a clause if and only if the principal's profits from entering the market are sufficiently large relative to the agent's outside option. If the principal can impose a fine on the agent for leaving the firm, she will never prefer a non-compete agreement.
Keywords: J3; M5; D86; D21; K1; 330; fine; incentives; incomplete contracts; non-compete agreements; option contract